2016
DOI: 10.11648/j.js.20160404.11
|View full text |Cite
|
Sign up to set email alerts
|

Common Nasal Anomalies and Its Implications on Intubation in Head and Neck Surgeries

Abstract: Nasotracheal intubation used to be the preferred route for prolonged intubation in critical care units. Nasotracheal intubation may sometimes cause nasal trauma. The study included one hundred and nine (109) adult patients, were scheduled for elective head and neck surgeries with general anaesthesia, requiring nasotracheal intubation. All the patients compiled the criteria of American Society of Anesthesiologists (ASA) physical status I and II were included in this study. The incidence of complicated laryngosc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Ramadhani reported sternomental distance as an indicator of head and neck mobility in 1996 (22). One study reported a signi cant difference in this anatomical distance between the single and multiple-attempt laryngoscopy groups (23). However, our study did not compare single and multiple attempts, and several factors, such as the di culty in evaluating neck mobility, may affect the results.…”
Section: Discussionmentioning
confidence: 67%
“…Ramadhani reported sternomental distance as an indicator of head and neck mobility in 1996 (22). One study reported a signi cant difference in this anatomical distance between the single and multiple-attempt laryngoscopy groups (23). However, our study did not compare single and multiple attempts, and several factors, such as the di culty in evaluating neck mobility, may affect the results.…”
Section: Discussionmentioning
confidence: 67%